(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Sickle cell anemia is a chronic disease and a blood disorder that induces cellular modification to the sickle-shaped form of defective hemoglobin in red blood cells. It is the most common genetic blood disease in the world. For people with sickle cell disease, it is important to explore non pharmacological treatments and use them as alternatives to drug treatments to relieve and treat acute and chronic pain. Methodology: A descriptive (quasi experimental) design. This study used a pretest, posttest I and posttest II with a design that is used is the one group. A non- probability sample of (30) mother was chose. Result: The findings of the study indicated that there was high significant difference among mother’s knowledge pretest and posttest I and posttest II at p-value =0.001. That indicates the effectiveness of educational program. Conclusion: The study concluded that there was no significant relationship between (age of mother, marital status, and Number of Pain Crises per Month) with mother’s knowledge also significance relationship between (level of education,) with mother’s knowledge. Recommendation: Frequent lectures and such educational program about non pharmacological to pain management should be implemented in Basra center for hereditary blood disease. Provide an educational booklet for mother includes information about sickle cell anemia and non-pharmacological to pain management. Real need for coordination with the media in order to increase mothers’ knowledge about non pharmacological to pain management.